2013
DOI: 10.4314/sajas.v43i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Should we reject animal source foods to save the planet? A review of the sustainability of global livestock production

Abstract: Within the next 40 years, the global livestock industry will have to considerably increase production in order to supply the population with animal-source foods, yet the industry must concurrently improve the three metrics of sustainability -economic viability, environmental stewardship and social responsibility. Environmental stewardship is currently the area for which animal agriculture is under the most scrutiny, as many consumers perceive that animal-source foods have an unacceptable environmental cost. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Productivity is significantly lower under organic management systems, with reductions in milk yield ranging from 15% to 27% (USDA, 2007). When differences in productivity are accounted for, organic dairy production requires considerably more feed, land and water resources per unit of milk, and has a greater environmental impact (Capper et al, 2008;Capper, 2013).…”
Section: Impact Of New Technology On the Environmentmentioning
confidence: 99%
“…Productivity is significantly lower under organic management systems, with reductions in milk yield ranging from 15% to 27% (USDA, 2007). When differences in productivity are accounted for, organic dairy production requires considerably more feed, land and water resources per unit of milk, and has a greater environmental impact (Capper et al, 2008;Capper, 2013).…”
Section: Impact Of New Technology On the Environmentmentioning
confidence: 99%
“…Subsequently, uncontrolled grazing became a serious problem in the riparian thereby affecting the farming and non-farming opportunities along the riparian on which most of the community's livelihood depends (Meagher and Yunusa, 2012). Thereby, studies carried out on livestock grazing (Capper, 2013, Scholtz.et al, 2013, IFAD, 2013 showed that there has been a major environmental impact of livestock on plant community, land, water and biodiversity.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Enhancing reproductive life of the doe can increase profits through increased sales (as fewer offspring are required as replacements), more selective culling (to increase health and productivity) [42] and herd expansion. Reproductive performance and a high rate of parturition are vital for continued lactation for dairy production, and to produce offspring for meat production [12]. Therefore optimising reproductive performance is essential for both diversification and intensification.…”
Section: Reproductionmentioning
confidence: 99%
“…Seven reproductive parameters were calculated, following Pittavino et al [11] (Table 2), as reproductive performance and a high rate of parturition are key drivers for continued lactation for dairy production and the production of offspring for meat production [12]. These reproductive parameters included herd fertility rate (the proportion of does becoming pregnant within a year), herd prolificacy (the ratio of kids born to the number of females becoming pregnant within a year; a prolificacy greater than one indicates the occurrence of multiple births by does), herd fecundity (the product of fertility and prolificacy, indicating the ratio between the number of kids born and the total number of does in the herd), new birth rate (the proportion of kids born that survive to weaning), herd reproduction rate (the product of new birth rate and fecundity, indicating the ratio of kids surviving to weaning to the total number of does in the herd), herd replacement rate (the rate that kids need to be introduced into the herd to replace all goats removed from the herd due to mortality, slaughter or sale; this is inversely proportional to the total number of kids surviving to weaning per doe lifetime), reproductive life of the doe (the number of years the doe is reproductively active for) and the lifetime productivity of the doe (the total number of surviving kids produced in a doe's lifetime).…”
Section: Calculation Of Reproductive Parametersmentioning
confidence: 99%